An Anatomical Variation of Median Artery of Forearm and Palm: Cadaveric Study into its Origin and Course - Khan, G. A.; Shrestha, A. (Kathmandu University Medical Journal, 2022)
Background The median artery (transitory artery) represents the forearm’s embryonic arterial axis. At 8th week of gestation retreats into a little canal that supplies the median nerve. Later, ulnar and radial arteries take its place. Adults may still have it in either a palmar or an antebrachial pattern. The persistent median arteries are a long, angular arterial that extends to the hand’s palmar surface. The median artery only partially recedes in the antebrachial type.Objective To identify the median artery distribution in the adult Nepalese population. Method Twenty-five adult human cadavers’ left and right upper limbs undergone to descriptive research. The persistent median artery was exposed according to the Cunningham’s Manual of Practical Anatomy.Result The forearm and hand arteries in each of the fifty upper limbs from the twenty-five formalin-embalmed human cadavers were studied. Among fifty upper limbs, persistent median arteries were found in six (twelve percent) of them. One percent of a cadaver’s right and left limbs had bilateral persisting median arteries (ante brachial). Persistent median artery of the ante brachial type that arises from the anterior interosseous artery in a right upper limb. Persistent median artery emerging from the posterior interosseous arteries were visible in one right upper limb.Conclusion The study showed persistent median artery of ante brachial type. The posterior interosseus artery is the source of the majority of antebrachial type. A median artery piercing the median nerve was discovered.